Forum: On Roudinesco’s Article “Psychoanalysts Have Contributed to Their Own Downfall” - Sophie Marret-Maleval; Aurélie Pfauwadel (EJP import test, 2019)
The “so-called decline” of psychoanalysis is a “false diagnosis”, assert in a Forum inLe MondeSophie Marret-Maleval and Aurélie Pfauwadel, psychoanalysts and university professors, in response to a text by Elisabeth Roudinesco published on February 9th2019.